ACOG Committee Statement No. 33: Updated Federal Regulation: The Pregnant Workers Fairness Act (PWFA) (Obstetrics & Gynecology, 2026)
In the United States, it is common for pregnant individuals to work outside the home. Working during pregnancy is generally safe. Before 2023, there were no federal protections guaranteeing comprehensive accommodation for pregnant and postpartum individuals. The Pregnant Workers Fairness Act (PWFA) is a federal law that requires covered employers to provide reasonable accommodations to workers with known limitations related to pregnancy, childbirth, and related medical conditions. This Committee Statement provides an overview of the law, including information on supporting documentation requirements, and highlights previous guidance on workplace safety during pregnancy that health care professionals can use to inform clinical recommendations for their patients and employers. Obstetrician–gynecologists and other obstetric care professionals play an important role in assisting patients in accessing workplace accommodations and in ensuring that patients are aware that they may have legal rights to accommodations and leave. Please see the American College of Obstetricians & Gynecologists' PWFA topic page for additional information about the federal law and regulations, sample accommodation notes, and other practical resources (http://www.acog.org/pwfa).